Implementasi Peraturan Menteri Pendidikan Dan Kebudayaan Republik Indonesia Nomor 8 Tahun 2020 di Sekolah Menengah Atas Negeri 8 Medan - Susiana Saragih; Warjio Warjio; Adam Adam (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
Regular School Operational Assistance (BOS) is a central government program to provide funding for operational costs for schools sourced from non- physical special allocation funds, in its implementation technically experiencing problems, including slow BOS management, misuse of the BOS budget, incomplete accountability reports and late data synchronization. SMA Negeri 8 is one of the school as recipients of the Regular School Operational Assistance in the city of Medan.This study aims to identify and analyze the policy implementation of the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 8 of 2020 concerning the Technical Guidelines for Regular School Operational Assistance at SMA Negeri 8 Medan and to find out what factors are obstacles/ obstacles in the implementation of the Regulation of the Minister of Education and Culture Number 8 Tahun 2020 regarding Regular School Operational Assistance Technical Guidelines.The research method used is a descriptive method with qualitative approach, with the research informants being the Regular BOS Team at SMA Negeri 8 Medan.The theory used is George C Edward III’s public policy theory. The influencing factors are communication, resources, disposition and bureaucratic structure. The results of this study indicate that The implementation of the regulation of the minister of education and culure of the Republic of Indonesia Number 8 of 2022 has been carried out but not yet with optimal results. The succes of policy implementation.